How does motor performance change with increasing stress doses? A tutorial on dose-response profiles applied to crew rowing - Hill, Y.; Cijpers, L. S.; Silva, P. L.; Hartigh, R. J. R. D.; Kiefer, A. W. (Brazilian Journal of Motor Behavior, 2023)
Many models of motor performance acknowledge that adapting to stressors plays a major role in how we move. However, most models lack a precise conceptualization of the way in which stress-response dynamics unfold. To fill this void, we first present popular models from the domain of biology and psychology which argue that the impact of a stressor depends on its dose. Next, we provide a tutorial using the example of crew rowing to demonstrate how these models can be scaled to human motor performance. In this example, the dose of the stressor is varied by target times for several 500 m races and the response variable represents the crew coordination. Specifically, we discuss how the necessary parameters can be determined a priori and how the data can be analyzed to pinpoint the exact dose-response relationship. These strides are necessary for developing more comprehensive theories of motor performance and engage in cross-disciplinary research on the impact of stressors.